Prevalence and factors associated with loneliness among Indonesian female adolescents: a cross-sectional study - Marthoenis; Dahlia; Jacqueline Nassimbwa (BMC, 2022)
Abstract Background Loneliness, or the perception of social disconnectedness, is a public health concern and is reported to be a frequent experience during adolescence (10-19 years). This study investigates the prevalence of loneliness and associated health-risk behaviors among Indonesian female adolescents. Methods This was a cross-sectional study, data for which were extracted from the WHO's Global School-based Student Health Survey (GSHS), which uses a globally standardized cross-sectional methodology to provide accurate data on behaviors and protective factors among students. Data from 4993 female students aged 13-17 years old from 74 schools were extracted from the 2015 survey in Indonesia and analyzed. Loneliness was used as a single measure, as happens in other studies using GSHS data. Descriptive analysis was done for age, socioemotional issues, health-risk behaviors, and contextual factors. This was followed by multiple logistic regression analysis to identify loneliness-associated factors. Results Approximately 6.5% of Indonesian female adolescents experience loneliness most of the time or always. Adolescents experiencing loneliness had a higher rate of sleep disturbance (37.6%), suicide ideation (21%), suicide plan (20.8%), smoking behavior (15%), and alcohol use (15.7%) than the general population. Multiple regression analysis confirms that adolescents who have no close friends, have been bullied during the past month, experience sleep disturbance, have had suicide ideation and suicide plans, are always feeling hungry, are exposed to passive smoking, and are engaged in a sedentary lifestyle are at a higher likelihood of suffering from loneliness (p < 0.05). On the other hand, having kind and helpful classmates served as a useful protection against loneliness (p < 0.05). Conclusions The rate of loneliness in Indonesian female adolescents is relatively lower than previously reported elsewhere. Several health-risk behaviors and contextual factors are associated with loneliness. It is important to gain insight into the exact interplay between factors and loneliness since that could inform future intervention development and lead to better well-being among female adolescents.